(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2024)
This paper undertook a cursory study at the extent of adult literacy attained through educational broadcasting in Nigeria. With a brief introduction on the origin and development of the concept of educational broadcasting in Nigeria. The paper highlights among others, the improvement in adult literacy in Nigeria through the effective utilization of educational broadcasting. The work identifies the importance of educational broadcasting to teaching and learning as a means of encouraging a greater understanding of a subject matter through the means of presentation which is always clear, straight forward and in simple language especially to the adults as target audience. Meanwhile, adult literacy or adult education is a practice in which adults engage in systematic and sustained self-educating activities in order to gain new forms of knowledge, skill, attitudes or values. It can entail any form of learning where adults and not children engage in beyond traditional schooling, encompassing basic literacy to personal fulfillment as a lifelong learner and to ensure the fulfillment of one’s desires as an individual. However, some of the challenges of educational broadcasting in improving the level of adult literacy were identified.Some of the problems as observed include among others erratic and irregular power supply, inadequate man power resources, equipment, poor storage, facilities and timing. Hence the work recommends that bearing in mind the imperatives of educational broadcasting as a means of improving literacy among the teaming illiterate adults in the country the Nigeria government at all levels: local, state and federal should not only improve on educational broadcasting but adequately channels the resources for its improved utilization. In addition, the government should ensure that experts and professionals in the field of educational broadcasting are well trained, employed and enumerated in areas where they are needed so as to solve the problem of human resources and manpower in the sector.